Multivocality of Saudi COVID-19 discourse in social media posts: a socio-semiotic multimodal perspective - Al-Ghamdi, Naimah Ahmad; Albawardi, Areej Hammad (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper examines the discourse of COVID-19 (also known as coronavirus) in social media posts and argues that the mediated COVID-19 discourse in Saudi Arabia enacted a variety of voices and thematic discourses that cannot be fully evaluated without reference to the locality of the sociolinguistic semiotics of the speech community. It attempts to construct the various non-verbal multivocalities in written and visual COVID-19 discourse present in 24 texts obtained from Saudi social media platforms, namely WhatsApp and Twitter, during the COVID-19 pandemic in the months of February, March and April, 2020. WhatsApp and Twitter are chosen because they are considered the platforms most used by Saudis in Saudi Arabia (GlobalWebIndex, 2020a, 2020b). The study employs a socio-semiotic approach to the analysis of collected data following Kress & Van Leeuwen (1996), mediated discourse analysis (Norris & Jones, 2005; Scollon, 2001) and systemic functional multimodal discourse analysis (SF-MDA). The analysis aims at integrating the social semiotics and multimodal approaches to better understand the dynamic Saudi discourse on COVID-19. The discourse on COVID-19 has revealed the dynamic multi-layered nature of governmental, individual and public voices pertaining to COVID-19 multi-discoursal themes, novel multimodal resources and the specific cultural semiotics of Saudi Arabia. The findings of the study revealed that the COVID-19 pandemic mediated discourse is relevant to the local speech community diglossic situation, cultural semiotics, social norms and integrated national identity.